Stem Cell Transplantation for Diamond-Blackfan Anemia. A Retrospective Study on Behalf of the Severe Aplastic Anemia Working Party of the European Blood and Marrow Transplantation Group (EBMT) - Miano, Maurizio; Eikema, Dirk-Jan; de la Fuente, Josu; Bosman, Paul; Ghavamzadeh, Ardeshir; Smiers, Frans; Sengeløv, Henrik; Yesilipek, Akif; Formankova, Renata; Bader, Peter; Díaz Pérez, Miguel Ángel; Bertrand, Yves; et al. (Transplantation and cellular therapy, 2021)
Data on stem cell transplantation (SCT) for Diamond-Blackfan Anemia (DBA) is limited. We studied patients transplanted for DBA and registered in the EBMT database. Between 1985 and 2016, 106 DBA patients (median age, 6.8 years) underwent hematopoietic stem cell transplantation from matched-sibling donors (57%), unrelated donors (36%), or other related donors (7%), using marrow (68%), peripheral blood stem cells (20%), both marrow and peripheral blood stem cells (1%), or cord blood (11%). The cumulative incidence of engraftment was 86% (80% to 93%), and neutrophil recovery and platelet recovery were achieved on day +18 (range, 16 to 20) and +36 (range, 32 to 43), respectively. Three-year overall survival and event-free survival were 84% (77% to 91%) and 81% (74% to 89%), respectively. Older patients were significantly more likely to die (hazard ratio, 1.4; 95% confidence interval, 1.06 to 1.23; P < .001). Outcomes were similar between sibling compared to unrelated-donor transplants. The incidence of acute grades II to IV of graft-versus-host disease (GVHD) was 30% (21% to 39%), and the incidence of extensive chronic GVHD was 15% (7% to 22%). This study shows that SCT may represent an alternative therapeutic option for transfusion-dependent younger patients.
Keywords: Congenital disorder; Stem Cell Transplantation; Diamond-Blackfan Anemia; aplastická anemie; Child; lidé; retrospektivní studie; Anemia, Aplastic; kostní dřeň; transplantace hematopoetických kmenových buněk; Anemia, Diamond-Blackfan; Bone Marrow; dítě; Hematopoietic Stem Cell Transplantation; Bone Marrow Failure; Retrospective Studies; Diamondova-Blackfanova anemie; Humans